The Effectof Experiential Learning-Based on Improving English Speaking Skills of Kindergarten Teachers - Tiyas Oktaviana; Ahmad Nur Syafiq; Anwari Anwari (Globish: An English-Indonesian Journal for English, Education, and Culture, 2026)
This research paper investigated the effectiveness of an Experiential Learning (EL) intervention on the English-speaking skills of kindergarten teachers at TK PAPB Semarang. Using a one-group pretest-posttest design with six teachers, the research assessed skills in pronunciation, intonation, fluency, and accuracy. Results showed a statistically significant improvement in overall speaking competence, with post-test scores increasing by an average of five points (p = 0.010). This confirms the EL approach, which utilized role-plays and simulations, was effective in enhancing teacher performance. However, high standard deviations in post-test scores, especially for pronunciation, indicated that significant ability disparities among participants persisted. The study concludes that while EL is a valuable strategy, future interventions should integrate more personalized, differentiated instruction to address the needs of heterogeneous learner groups.